The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1750-9378-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection and phylogenetic analysis of HPV-16 E6 variants among infected women from Northern Brazil

Abstract: BackgroundThe main cause of cervical cancer in the world is high risks human papillomavirus infection (mainly represented by HPV-16 and HPV-18), that are associated to the development of malign transformation of the epithelium. HPV prevalence exhibits a wide geographical variability and HPV-16 variants have been related to an increased risk of developing cervical intraepithelial lesion. The aim of this study was to describe DNA-HPV prevalence and HPV-16 variants among a women population from Northern Brazil.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
7
1
1
Order By: Relevance
“…In Brazil, there is considerable variation in the prevalence of HPVs and the distribution of genotypes. The prevalence recorded here was much higher than that found in previous studies in southern (6.7 %) [ 17 ] and southeastern Brazil (11 %) [ 18 ], but lower than that described in a previous study in northern Brazil (29.4 %) [ 19 ]. However, all these previous studies recorded HPV-16 as the most prevalent genotype, whereas in the present study, HPV-61 and HPV-82 were the most common, although HPV-16 was the most frequent hrHPV genotype, together with HPV-59.…”
Section: Discussioncontrasting
confidence: 81%
“…In Brazil, there is considerable variation in the prevalence of HPVs and the distribution of genotypes. The prevalence recorded here was much higher than that found in previous studies in southern (6.7 %) [ 17 ] and southeastern Brazil (11 %) [ 18 ], but lower than that described in a previous study in northern Brazil (29.4 %) [ 19 ]. However, all these previous studies recorded HPV-16 as the most prevalent genotype, whereas in the present study, HPV-61 and HPV-82 were the most common, although HPV-16 was the most frequent hrHPV genotype, together with HPV-59.…”
Section: Discussioncontrasting
confidence: 81%
“…Although the identification of HPV16 variants in our study was done by assaying the E6 gene sequence, our results showed that all HPV16-positive samples were of the European variant, which was consistent with previously described results in America 23 . A study from Brazil observed that 29.4 per cent of women with normal cytology were HPV positive, with HPV16 being the most commonly observed genotype (14%), followed by HPV-52 and HPV-45 24 . In these studies, the observed HPV16 variants were classified predominantly as European (87.5%), but Asian, African and American variants were also reported 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A study from Brazil observed that 29.4 per cent of women with normal cytology were HPV positive, with HPV16 being the most commonly observed genotype (14%), followed by HPV-52 and HPV-45 24 . In these studies, the observed HPV16 variants were classified predominantly as European (87.5%), but Asian, African and American variants were also reported 24 . In our study, HPV16 was also the primary viral genotype detected, followed by HPV18.…”
Section: Discussionmentioning
confidence: 99%
“…Isso está de acordo com os dados da literatura que mostram que esse genótipo está relacionado com a transmissão vertical 6,7 . Os outros dois genótipos encontrados (HPV-16 e HPV-18) são descritos na literatura como os mais frequentes 23,24 . Nas amostras de placenta e do sangue do cordão umbilical provenientes de uma parturiente, a determinação do genótipo não foi possível devido à sobreposição dos picos das sequências, o que indica a infecção por múltiplos genótipos 25 .…”
Section: Discussionunclassified